FENOMENA POPULARITAS MCDONALD’S SEBAGAI PILIHAN MAKANAN CEPAT SAJI BAGI GENERASI MUDA - Ulfaoktafia Ulfaoktafia; Istiana Aulia Sari; Elkin Rilvani; Listian Ahmad (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
The development of modern lifestyles has encouraged an increase in fast-food consumption among society, especially among young people. Easy access, practicality, and the influence of technological advancements and social media have made fast-food restaurants one of the most popular dining choices. One of the fast-food restaurant brands that has gained a high level of popularity among young consumers is McDonald's. This study aims to understand the phenomenon of McDonald's popularity as a fast-food choice among the younger generation. The research employed a descriptive qualitative method, with data collected through interviews with several informants categorized as young consumers who had consumed McDonald's products. In addition, the study was supported by a review of relevant literature. Data analysis was conducted using the Miles and Huberman model, which consists of data reduction, data presentation, and conclusion drawing. The findings indicate that the main factors influencing young people to choose McDonald's are the taste and consistency of its products, relatively affordable prices, easy accessibility, good service quality, and the influence of promotions and information disseminated through social media. The results also reveal that social media plays an important role in shaping positive perceptions and increasing young consumers' interest in McDonald's. Therefore, the popularity of McDonald's among the younger generation is the result of a combination of product quality, service quality, brand image, accessibility, and effective digital marketing strategies.